Variability of fiber content in the stems of different varieties of fiber flax - T. A. Rozhmina; A. A. Yanyshina (Аграрная наука Евро-Северо-Востока, 2023)
The analysis of experimental data on the evaluation of seed lots of fiber flax of domestic varieties for genetic uniformity by the method of soil control according to the trait "fiber content in the stem" for the period from 1953 to 2022 was carried out. Seed material for evaluation was obtained from breeding and seed-growing institutions in Russia, Belarus, Ukraine, Lithuania, Latvia and Estonia.   The purpose of the research was to assess the level of variability of the trait "fiber content in the stems" of fiber flax and the effectiveness of domestic breeding in this direction for 70 years.   Using the Svetoch variety as an example, it was shown that the differences between seed lots (from 4 to 11 lots of various scientific institutions were estimated annually) based on the results of 13 years of testing ranged from 0.4 to 2.5 abs. percent within one year, the coefficient of variation was from 0.52 to 3.14 %, which indicated the high stability of this trait. At the same time, the value of the trait in this variety, depending on the growing conditions for the period from 1953 to 1972 ranged from 27.9 to 35.4 %, the coefficient of variation on average over 20 years was 6.8 %, the average value of the trait was 31.7 %. In variety Tomsky 18, for the period of testing from 1993 to 2022, the value of the trait was in the range from 25.5 to 35.0 % (Cv = 8.4 %). The biological potential of modern varieties of fiber flax – Krom, A-29, Diplomat, Cesar, Visit and Tomsky 17 made it possible to obtain a fiber content in the stem in some years at the level of 38.1...39.8 %, with an average value of the trait – 32.8…35.2 % (Cv = 9.6…14.9 %). The highest and most stable fiber content in the stem of 36 studied modern domestic varieties of fiber flax was found in Sursky variety, in which the value of the trait on average over the years of testing was 34.5 %, the coefficient of variation was 6.4 %, which indicated a high level of adaptability.